The Observed Seasonal Cycle of Submesoscale Processes in the Antarctic Marginal Ice Zone. Issue 6 (7th June 2020) - Biddle, L. C.; Swart, S.
Abstract: Submesoscale flows are energetic processes in the upper ocean that occur at scales of a few kilometers. These phenomena are important to climate because they can strongly impact vertical motions of heat, carbon, and biogeochemical properties between the surface and deep ocean. Their presence and magnitude are poorly understood in the Antarctic marginal ice zone (MIZ) and under sea ice due to a lack of observations. We present tagged southern elephant seal hydrographic data from the eastern Weddell Sea, over the austral late summer to spring in 2008, to assess the magnitude and seasonality of submesoscale processes in the Antarctic MIZ. We consider the linkages between sea ice cover, ocean stress variability, and mixed layer depth and how these influence the submesoscale fluxes. We find that there is a strong seasonal cycle in the magnitude of the equivalent heat flux from submesoscale flows (240 Wm −2 ), with peak activity occurring in midwinter. Periods of increased variability in sea ice cover, likely associated with leads, are also linked to restratification through submesoscale fluxes in midwinter. These findings have implications for understanding the magnitude and variability of upper ocean stratification and therefore highlights the importance of developing parameterizations for submesoscale processes in the Antarctic MIZ within global climate models. Plain Language Summary: Changes in the mixed layer depth can affect vertical transport of heat and carbon from the atmosphere into the deep ocean. Submesoscale processes, occurring on small time and space scales of hours–days and a few kilometers, can directly impact these mixed layer depth changes. Understanding the magnitude and activity of submesoscale flows is critical to improve our knowledge of how the climate may change in the future, yet there are currently no reports of them in the Southern Ocean under sea ice. Using instrumented seals, we present the first known observations of submesoscale fluxes from late austral summer through to spring in and near Antarctic sea ice. Our findings show that these small‐scale processes can have a strong effect on the upper ocean and can cause the mixed layer depth to shoal even in the middle of winter. There is also a clear seasonal cycle in the magnitude of the submesoscale activity. This study indicates that submesoscale processes should not be overlooked as a critical component of upper ocean processes in the Antarctic sea ice zone. Key Points: Hydrographic data from tagged seals are used to observe submesoscale processes in the Antarctic Marginal Ice Zone We find a strong seasonal cycle in the magnitude of submesoscale flows under/within sea ice, with a peak in midwinter Mixed layer instabilities show the largest seasonality, while wind‐driven frontal flows are dampened by the presence of sea ice